A “Near-Miss Lethal Accident Case” in MR Suit of a Tertiary Care Hospital - Samina Mufti; Mushtaq A. Sheikh; Abdul Hakim; Showkat A. Mufti; Farooq Jan (Case Reports in Radiology)
A “near miss” is an unpleasant event that did not result in injury, illness, or damage but had the potential to do so, but for a fortunate break in the chain of events. We present a near-miss case which occurred in the MR suite of a tertiary care hospital. Although the MR is considered a very safe procedure, if MR safety guidelines are not adhered to, adverse and catastrophic events to the extent of patient deaths are known to have occurred. It is hoped that this incident will prompt hospitals to document and follow MR safety protocols for patient and staff safety. Although MRI is an extremely safe procedure rarely MR adverse incidents have resulted in serious physical injury or even death. The incident is an eye opener regarding potential adverse events lurking in the relatively safe MR environment and provides an opportunity to rectify the inadequacies in MR safety.